Survival, behavioural changes and geotaxis response of 𝘊𝘶𝘭𝘦𝘹 SP. Larvae (CULICIDAE) after exposure to carbaryl and pymetrozine - Radebe, Nonhlahla (University of the Free State, 2024)
Pesticides play a crucial role in agriculture and are extensively used in developing countries to ensure food security and economic prosperity. However, as the climate is changing (rise in temperature and precipitation), the efficacy of pesticides is reduced leading to more frequent application and extensive use of pesticides causing greater adverse effects on aquatic systems. South Africa is not spared from this pesticide pollution. To mitigate the environmental effects of pesticides in South Africa, (particularly QwaQwa where many farms are situated), the least toxic pesticides such as pymetrozine (a selective “Environmental Protection Agency Reduced Risk pesticide”) should be preferably used and recommended for Integrated Pesticides Management (IPM) whereas highly toxic ones such as carbaryl should be phased out to reduce pesticide pollution and unintended death of non-target aquatic organisms. The present comparative study aimed to evaluate the effects of carbaryl and pymetrozine on the behaviour of mosquito larvae (𝘊𝘶𝘭𝘦𝘹 sp.). Mortality experiments showed that carbaryl (0, 12.50, 25, 50 and 100 µg/L) caused more mortality than pymetrozine (0, 6.25, 12. 50, 25 and 50 mg/L), and exposure to both insecticides altered the breathing, swimming and resting behaviours of the mosquito larvae. There was mortality in all tested concentrations, except for distilled water (control). The highest mortality was recorded in 100 µg/L of carbaryl. Carbaryl had an LC₅₀ of 0.028 mg/L, whereas pymetrozine generated a lethal concentration 50 (LC₅₀ of 181.950 mg/L, this proves the high toxicity of carbaryl as the LC₅₀ of carbaryl is more than 100 times smaller than that of pymetrozine. The larvae spent more time breathing in the absence of these insecticides, more time swimming in the presence of carbaryl and more time resting in the presence of pymetrozine. Moreover, these toxicants altered the geotaxis of these organisms thus compromising their fitness. The larvae predominantly displayed negative geotaxis (spent more time breathing) when exposed to both these insecticides. From these findings, it can be noted that pymetrozine was the least toxic of the two pesticides. Hence, pymetrozine can be recommended for IPM. This was supported by a systematic review of 24 years of carbaryl effects on insect behaviour. The overall results revealed that carbaryl should be phased out in favour of less toxic yet effective insecticides like pymetrozine.
Keywords: Behaviour; Carbaryl; Climate change; Culicids; Pollution; Pymetrozine